PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN KONSUMEN KARTU PRABAYAR SIMPATI(Studi Kasus Pada Pemakai Kartu Prabayar Simpati Di Fakultas Ekonomi Universitas Negeri Surabaya) - SOLIKHA, MUKHFIDHATUS (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Based on the observations or the observations of researchers that students at the Faculty of Economics, the most used prepaid cards Simpati they consider a prepaid card and the phone cheap SMS rates, the most extensive network and coverage compared to other carriers products, though not the majority, and is the most widely used by young people, especially students of the Faculty of Economics, State University of Surabaya is a competitor Simpati namely IM3, this study is unique, because the uniqueness that is the challenge for researchers and is expected to become an important record, and the results of this study will ultimately attract concluded. research objectives to be achieved by the authors is to determine whether the services marketing mix which includes product, price, distribution channels, promotion, people, processes and customer service have a significant effect either partially or simultaneously to customer satisfaction Simpati prepaid cards. Keywords: Services Marketing Mix and Customer Satisfaction